2014
DOI: 10.3390/ijerph110403982
|View full text |Cite
|
Sign up to set email alerts
|

The Lag Effects and Vulnerabilities of Temperature Effects on Cardiovascular Disease Mortality in a Subtropical Climate Zone in China

Abstract: This research quantifies the lag effects and vulnerabilities of temperature effects on cardiovascular disease in Changsha—a subtropical climate zone of China. A Poisson regression model within a distributed lag nonlinear models framework was used to examine the lag effects of cold- and heat-related CVD mortality. The lag effect for heat-related CVD mortality was just 0–3 days. In contrast, we observed a statistically significant association with 10–25 lag days for cold-related CVD mortality. Low temperatures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 40 publications
6
46
0
1
Order By: Relevance
“…The results showed that the heat thresholds were 29 • C, 29 • C, 29 • C, and 30 • C and the cold thresholds were 6 • C, 10 • C, 14 • C, and 15 • C for Hefei, Changsha, Nanning, and Haikou, respectively. Previous studies showed that the temperature threshold effect exhibits spatial heterogeneity [19][20][21][22][23]. We compared the results with previous studies that were conducted in East Asia.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The results showed that the heat thresholds were 29 • C, 29 • C, 29 • C, and 30 • C and the cold thresholds were 6 • C, 10 • C, 14 • C, and 15 • C for Hefei, Changsha, Nanning, and Haikou, respectively. Previous studies showed that the temperature threshold effect exhibits spatial heterogeneity [19][20][21][22][23]. We compared the results with previous studies that were conducted in East Asia.…”
Section: Discussionsupporting
confidence: 58%
“…Next, we calculated temperature thresholds for the four cities. The previous research showed that the association between temperature and CVD mortality was U shaped [19,25]; therefore, we used the double threshold-natural cubic spline DLNM from a previous study [17]. We assumed both heat-and cold-related CVD mortality were linear, and the temperature thresholds were calculated as previously described [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distributed lag nonlinear model (DLNM) is used to describe the nonlinear associations between high temperature and mortality and lag response (Gasparrini et al, 2015). Specifically, we estimated the temperature-effect with a maximum of a two-day lag, as previous studies indicated that the effects of high temperatures were generally of the short-term (Chen et al, 2013; Guo et al, 2014; Huang et al, 2014); in the cross-basis function, three internal knots were placed at the quartiles, and one internal knot was placed at equally spaced values on the log scale (Gasparrini et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…According to previous studies, the temperature variability had delayed effect on health 18. The study conducted by Huang et al 30 showed that the effect of the cold temperatures had a long lag period of 10–25 days, while hot temperatures had a short lag period of only 1–3 days. The ageing phenomena induces some physiological changes in thermoregulation and homeostasis, along with the prevalence of chronic conditions, which cause vulnerability to cold and heat 26…”
Section: Discussionmentioning
confidence: 97%